Bed-parallel slip: Identifying missing displacement in mass transport deposits. (February 2020) - Alsop, G.I.; Weinberger, R.; Marco, S.; Levi, T.
Abstract: Bed-parallel slip (BPS), where neighbouring beds slide past one another along bedding planes, is notoriously difficult to identify without reference to pre-existing features such as steep faults or dykes that act as markers to record BPS offset. While BPS is intuitively thought to operate during downslope sliding of mass transport deposits (MTDs) in sedimentary basins, there is a conspicuous lack of supporting outcrop or seismic data to corroborate this and BPS displacement may therefore have remained unaccounted for. This study addresses this gap in knowledge by investigating late-Pleistocene MTDs developed around the Dead Sea Basin and provides the first detailed analysis of BPS that pervades a gravity-driven setting. In particular, we examine the role of BPS that crosscuts earlier normal and reverse faults that act as markers to allow metre-scale patterns of horizontal displacement to be identified in MTDs. The studied BPS always forms with a consistent top-to-the east sense of offset that corresponds with gravity-driven downslope movement towards the depo-centre of the basin. BPS frequently develops adjacent to competent detrital-rich beds and forms discrete glide planes with little or no visible deformation in sediments on either margin, although detachment folds are occasionally developed above the slip plane and confirm directions of easterly movement. Early downslope-dipping normal faults that are cut by later BPS planes results in older over younger stratigraphic relationships across the BPS surface, together with 'sawtooth' patterns where multiple BPS planes have developed. Conversely, early upslope-dipping normal faults that are cut by BPS create younger over older stratigraphic relationships combined with missing section and 'staircase' patterns where multiple BPS planes exist. As BPS in sub-horizontal sequences does not have a vertical component of displacement, it may be examined in terms of horizontal 'heave'. BPS increases heave in upslope-dipping normal faults, whereas it reduces heave in downslope-dipping normal faults and may even become negative where sections are repeated across sawtooth profiles. In addition, BPS increases heave in upslope-dipping reverse/thrust faults and reduces heave across downslope dipping 'backthrusts'. Although individual BPS planes may have limited displacement, the net consequence of multiple planes of BPS that form in the shallow-subsurface is to distort patterns and estimates of extension and contraction across fault zones in MTDs. Highlights: This work forms the first detailed study that documents, describes and distinguishes the effects of gravity-driven bed-parallel slip (BPS) on early normal and reverse faults in mass transport deposits (MTDs). We establish a geometric framework that incorporates four possible overprinting relationships depending on if the hangingwall of later BPS has moved in the same (synthetic) or opposite (antithetic) sense to earlier faults. The position of BPS planes is controlled by detrital-rich beds that trap underlying fluids. Where BPS comprises two surfaces that utilise the same displaced marker bed either side of an early fault, then one BPS plane must propagate downslope and the other upslope. Typical relationships are reversed across BPS planes such that telescoped normal faults are marked by older over younger beds, whereas BPS cutting backthrusts results in younger over older stratigraphy.